2011
DOI: 10.1149/1.3517147
|View full text |Cite
|
Sign up to set email alerts
|

Non-Contact and Non-Destructive Characterization Alternatives of Ultra-Shallow Implanted Silicon p-n Junctions by Multi-Wavelength Raman and Photoluminescence Spectroscopy

Abstract: Ultra-shallow boron implanted ͑B + 1 keV 1.0 ϫ 10 15 cm −2 ͒ n-type Si wafers were prepared and characterized by multiwavelength Raman and photoluminescence ͑PL͒ spectroscopy before and after rapid thermal annealing ͑RTA͒. The Raman and PL characterization results were compared with sheet resistance from four point probe measurements and boron depth profiles from secondary ion mass spectroscopy. We have found a very strong correlation between the rapid, non-contact optical characterization results and importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…2,3,5,[9][10][11] Figure 3a shows 650 nm excited RTPL spectra from the 75 s annealed wafers at temperatures between 350…”
Section: Resultsmentioning
confidence: 99%
“…2,3,5,[9][10][11] Figure 3a shows 650 nm excited RTPL spectra from the 75 s annealed wafers at temperatures between 350…”
Section: Resultsmentioning
confidence: 99%
“…The details of the system and its applications have been published elsewhere. [7][8][9][10] No measurable RTPL signal was observed from most of SiO 2 /Si wafers under 532 nm excitation. For 650 nm excitation, the laser power at the wafer surface was 20 mW and exposure time was 1.0 s per point.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 Promising results of RT spectroscopic PL studies on ultra-shallow and shallow implanted junctions have also been reported previously. [19][20][21][22] RTPL characterization of non-radiative defect density on surfaces and interfaces of Si with native, anodic and thin thermal oxides, have been extensively studied under ultra violet (UV) excitation in vacuum by Timoshenko et al 23 In this paper, RTPL was investigated using implant annealed Si samples, which showed electrical performance variations, even though all the (implant and anneal) process conditions are substantially the same. The major objectives are to understand the main cause of electrical performance variations and develop a practical implant monitoring technique for CMOS image sensor process control.…”
mentioning
confidence: 99%
“…Interband RTPL has also been used in monitoring surface and interface defects during oxidation, epitaxial Si quality and electrical activation of low energy implanted Si after RTA. [17][18][19][20][21][22][23] The effective lifetime in semiconductors is important to the operation of some semiconductor devices such as solar cells, pn junctions, bipolar junction transistors and thyristors, but it is generally difficult to decompose into bulk recombination lifetime and surface recombination velocity. 25,26 Correlation lifetime and PL intensity near 1.1 μm has been studied in bulk Si and SOI (silicon-on-insulator) wafers under various excitation wavelengths.…”
mentioning
confidence: 99%